Exploring The Pedagogical Function and Students Perception of Code-Switching in an Indonesian EFL Classroom - Honey Ramadhani; Novia Trisanti (IKIP Siliwangi, 2026)
This study explores the pedagogical functions of code-switching and students’ perceptions of its use in an Indonesian EFL classroom. Using a qualitative case study design, the research involved one English teacher and approximately 30 seventh-grade students at a public junior high school in Semarang, Indonesia. Data were collected through classroom observations, semi-structured interviews, and document analysis, then analyzed using thematic analysis. The findings demonstrated that the teacher employed code-switching to explain difficult material, give instructions, manage classroom interaction, and support students’ comprehension. Code-switching occurred most frequently during explanation and instruction stages, especially when students were confused or had trouble understanding English. Although the teacher stated that code-switching was used spontaneously rather than as a planned strategy, classroom observations revealed that code switching consistently appeared in specific teaching contexts. Students generally perceived code-switching positively because it helped them understand the material more easily, reduced anxiety, increased confidence, and encouraged classroom participation. The study suggests that code-switching serves as an effective and responsive pedagogical strategy that supports students’ comprehension and engagement, particularly for learners with low English proficiency in EFL classrooms.